CONSEQUENCES OF BREXIT ON THE COMPETITION LAW AND POLICY OF THE UNITED KINGDOM AND THE EUROPEAN UNION - Mojašević, Aleksandar; Stefanovic, Stefan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The subject matter of this paper is the short-term and long-term consequences of Brexit − a historical event and a turning point in the development of the European Union (EU), for the United Kingdom (UK), and the EU competition law and policy. A comparative analysis of the historical development of legal regulation of competition in the UK and the EU, with a presentation of relevant cases from the practice of competition authorities, has been given at the beginning of the paper. A special emphasis was placed on the decisions of the European Commission regarding the anti-cartel policy. To what extent Brexit will influence the mergers and acquisitions policy, antitrust policy, anti-cartel policy, and state aid policy in the UK and the EU, are the topics covered in this paper. The central question refers to the extent of Brexit's influence on the change of UK and EU business environment and the repercussions that this change will have for the competition law. Finally, concluding remarks are given regarding the direction of future development of the UK competition law, i.e. whether and to what extent the UK law will be harmonized with the EU competition law and case law in this area, or there will be a radical turn towards adopting a completely new concept of competition law and policy.
Keywords: Brexit; UK competition law; EU competition law; short-term consequences; long-term consequences